The steroid metabolite 16(β)-OH-androstenedione generated by CYP21A2 serves as a substrate for CYP19A1. Issue 167 (March 2017) - Neunzig, J.; Milhim, M.; Schiffer, L.; Khatri, Y.; Zapp, J.; Sánchez-Guijo, A.; Hartmann, M.F.; Wudy, S.A.; Bernhardt, R.
Graphical abstract: Highlights: Novel activity of CYP21A2 elucidated. Discovery of the steroid intermediate 16beta-hydroxy-androstenedione. Potential diagnostic marker for endocrine diseases found. New substrate for CYP19A1 identified. Potential aromatase inhibitor found. Abstract: The 21-hydroxylase (CYP21A2) is a steroidogenic enzyme crucial for the synthesis of mineralo- and glucocorticoids. It is described to convert progesterone as well as 17-OH-progesterone, through a hydroxylation at position C21, into 11-deoxycorticosterone (DOC) and 11-deoxycortisol (RSS), respectively. In this study we unraveled CYP21A2 to have a broader steroid substrate spectrum than assumed. Utilizing a reconstituted in vitro system, consisting of purified human CYP21A2 and human cytochrome P450 reductase (CPR) we demonstrated that CYP21A2 is capable to metabolize DOC, RSS, androstenedione (A4) and testosterone (T). In addition, the conversion of A4 rendered a product whose structure was elucidated through NMR spectroscopy, showing a hydroxylation at position C16-beta. The androgenic properties of this steroid metabolite, 16(β)-OH-androstenedione (16bOHA4), were investigated and compared with A4. Both steroid metabolites were shown to be weak agonists for the human androgen receptor. Moreover, the interaction of 16bOHA4 with the aromatase (CYP19A1) was compared to that of A4, indicating that the C16 hydroxyl group does not influence the binding with CYP19A1. In contrast, the elucidation of the kinetic parameters showed an increased K m and decreased k cat value resulting in a 2-fold decreased catalytic efficiency compared to A4. These findings were in accordance with our docking studies, revealing a similar binding conformation and distance to the heme iron of both steroids. Furthermore, the product of 16bOHA4, presumably 16-hydroxy-estrone (16bOHE1), was investigated with regard to its estrogenic activity, which was negligible compared to estradiol and estrone. Finally, 16bOHA4 was found to be present in a patient with 11-hydroxylase deficiency and in a patient with an endocrine tumor. Taken together, this study provides novel information on the steroid hormone biosynthesis and presents a new method to detect further potential relevant novel steroid metabolites.